Impacto de la pandemia por SARS Cov2 en la adherencia al tratamiento en pacientes con hipertensión arterial de la parroquia El Sagrario y barrios aledaños de Loja - Toro Paladines, Diego Andrés (2023)
One in four adults worldwide suffers from hypertension. This condition is responsible for half of all deaths from heart attack and heart disease. With the advent of the SARS-CoV-2 pandemic, these people were at increased risk of severe disease and death. Therefore, the objective of this study was to analyze the impact of the SARS-CoV-2 pandemic on treatment adherence among people over 45 years of age diagnosed with hypertension in El Sagrario district and surrounding neighborhoods of Loja. A quantitative, descriptive, and cross-sectional methodology was used, with 170 individuals interviewed using the Morisky Green Levine Medication Adherence Scale and the Bonilla Test modified by Ortiz. The results of this study showed that most of the respondents had a correct adherence to treatment, and it was found that the factors that influenced the non-adherence to treatment were the high cost of medication, the lack of medicines in health centers, and difficulties in modifying their diet and exercise. It is concluded that adherence to antihypertensive treatment was similar to that found before the SARS-CoV-2 pandemic outbreak